Analisis pengukuran kinerja di Mall Pelayanan Publik Bone Bolango menggunakan metode balanced scorecard - Nadjamuddin, Difa Nurul Asyifah; Lahay, Idham Halid; Uloli, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Services to the community can be categorized as effective and efficient if the community gets easy service with short, fast, precise and satisfying procedures. However, the reality in the field is not as expected. Therefore, it is very important for the management of the Public Service Mall to evaluate its employees, to improve the quality of services provided to the community. This study aims to analyze and measure the performance of the Bone Bolango Public Service Mall office using the Balanced Scorecard method integrated with the AHP method. Based on the results of performance measurements at the Bone Bolango Public Service Mall using the Balanced Scorecard, the Financial Perspective in 2022 has a budget of Rp. 3,858,495,244 and a budget realization of Rp. 3,207,456,588 and in 2023 have a budget of 3,266,721,230 and a budget realization of Rp. 3,118,145,314